The Immunopathology of Multiple Sclerosis: An Overview - Lassmann, Hans (Brain Pathol, 2007)
Multiple sclerosis (MS) is traditionally seen as an inflammatory demyelinating disease, characterized by the formation of focal demyelinated plaques in the white matter of the central nervous system. In this review we describe recent evidence that the spectrum of MS pathology is much broader. This includes demyelination in the cortex and deep gray matter nuclei, as well as diffuse injury of the normal‐appearing white matter. The mechanisms responsible for the formation of focal lesions in different patients and in different stages of the disease as well as those involved in the induction of diffuse brain damage are complex and heterogeneous. This heterogeneity is reflected by different clinical manifestations of the disease, such as relapsing or progressive MS, and also explains at least in part the relation of MS to other inflammatory demyelinating diseases.